Penerapan Metode SAS untuk Meningkatkan Keterampilan Menulis Huruf Tegak Bersambung Kelas 1 SD - Ratna Putri Aulia; Ahmad Taufiq; Muh. Arafik; Ratna Putri Aulia; Ahmad Taufiq (Universitas Negeri Malang, 2021)
Abstract: This research aims to provide a contribution for students and teachers of grade 1, as well as for schools. The purpose of the research for students is to provide students with a learning experience in writing cursive letters and foster students’ enthusiasm for learning and improving cursive writing skills. Another research which is to become input for teachers in overcoming students' difficulties when learning to write cursive letters, can also be used by teachers as a reference for the development of learning to write cursive letters and can increase teacher’s creativity in managing learning to write cursive letters. For schools, this research aims to assist in improving the quality of education. The type of research used is Classroom Action Research (CAR). The subjects of this research namely teachers and students of grade 1, as well as the principal. Data collection techniques used are observation, tests, interviews, and documentation. Data analysis techniques used in the form of qualitative data analysis and quantitative data analysis. For the analysis of qualitative data obtained from data collection and analysis of quantitative data obtained from the processed results of the writing test in cursive with the SAS method. The result of research obtained showed that the percentage of student learning completeness in implementation of the second cycle reached 77,8 percent. Previously, precycle and first cycle activities were carried out, each of which the percentage of learning completeness was only 18,5 percent and 37 percent, and increased in the implementation of the second cycle. This shows that the application of the SAS method can improve the cursive writing skills of grade 1 students. Suggestion for students in the result of this study, namely that students should focus and actively ask the teacher when learning to write cursive letters, so that they can improve their writing skills. In addition, suggestions for teachers should use variations in learning so that students are more enthusiastic about writing cursive letters, and also give more attention to students who have not yet completed writing cursive letters. Abstrak: Penelitian ini bertujuan untuk memberikan kontribusi bagi siswa dan guru kelas 1, maupun bagi sekolah. Tujuan penelitian bagi siswa, yaitu dapat memberikan pengalaman belajar siswa dalam menulis huruf tegak bersambung dan menumbuhkan semangat belajar siswa untuk meningkatkan keterampilan menulis huruf tegak bersambung. Tujuan penelitian lainnya, yaitu menjadi bahan masukan untuk guru dalam mengatasi kesulitan siswa saat pembelajaran menulis huruf tegak bersambung, juga dapat dimanfaatkan oleh guru sebagai salah satu acuan untuk pengembangan pembelajaran menulis huruf tegak bersambung, dan dapat meningkatkan kreativitas guru dalam mengelola pembelajaran menulis huruf tegak bersambung. Bagi sekolah, penelitian ini bertujuan untuk membantu dalam meningkatkan mutu pendidikan. Jenis penelitian yang digunakan, yaitu Penelitian Tindakan Kelas (PTK). Subjek penelitian ini, yaitu guru dan siswa kelas 1, serta kepala sekolah. Teknik pengumpulan data yang digunakan yakni observasi, tes, wawancara, dan dokumentasi. Teknik analisis data yang digunakan berupa analisis data kualitatif dan analisis data kuantitatif. Untuk analisis data kualitatif diperoleh dari pengumpulan data dan analisis data kuantitatif diperoleh dari olahan hasil tes menulis huruf tegak bersambung dengan metode SAS. Hasil penelitian diperoleh persentase ketuntasan belajar siswa pada pelaksanaan siklus II yang mencapai 77,8 persen. Sebelumnya, dilakukan kegiatan pra siklus dan siklus I yang masing-masing perolehan persentase ketuntasan belajar hanya 18,5 persen dan 37 persen, dan meningkat pada pelaksanaan siklus II. Hal ini menunjukkan bahwa penerapan metode SAS ini dapat meningkatan keterampilan menulis huruf tegak bersambung siswa kelas 1. Saran bagi siswa dalam hasil penelitian ini, yaitu sebaiknya siswa fokus dan aktif bertanya kepada guru saat pembelajaran menulis huruf tegak bersambung, sehingga dapat meningkatkan keterampilan menulisnya. Selain itu, saran bagi guru sebaiknya menggunakan variasi dalam pembelajaran agar siswa semakin bersemangat untuk menulis huruf tegak bersambung, dan juga memberikan perhatian lebih kepada siswa yang belum tuntas dalam menulis huruf tegak bersambung.